Combination of Deauville score and quantitative positron emission tomography parameters as a predictive tool of anti‐CD19 chimeric antigen receptor T‐cell efficacy. Issue 2 (17th November 2022) - Guidetti, Anna; Dodero, Anna; Lorenzoni, Alice; Pizzamiglio, Sara; Argiroffi, Giovanni; Chiappella, Annalisa; Bagnoli, Filippo; Marasco, Vincenzo; Carniti, Cristiana; Monfrini, Chiara; Seregni, Ettore; Pennisi, Martina; et al.
Abstract: Background: Autologous anti‐CD19 chimeric antigen receptor (CAR) T‐cell therapy is an effective treatment for approximately 40% of relapsed/refractory large B cell lymphomas (LBCL), and early identification of patients at risk for relapse or progression after CAR T‐cell therapy represents a clinical need. Methods: The authors conducted a single‐center prospective study on 47 relapsed/refractory LBCL receiving CAR T‐cell therapy to evaluate the prognostic value of baseline and after infusion 18 F‐fluorodeoxyglucose positron emission tomography (PET)‐computed tomography. Qualitative and quantitative metabolic parameters were evaluated before lymphodepletion, at day 30 and 90 post‐infusion. Results: Deep variation of standardized uptake value (SUV)mean between baseline and day 30 correlated with response at day 90 (hazard ratio [HR], 1.49; 95% confidence interval [CI], 1.01–2.2); p = .04) and better progression‐free survival (PFS) (HR, 0.63; 95% CI, 0.41–0.97); p = .04). In the overall population, 1‐year PFS was 63% for Deauville score (DS)1–3 and 39% for DS4–5 patients, respectively ( p = .02), however, the prognostic role of DS was lost when survivals are analyzed by considering 38 patients not progressing at 30 days. In these patients, in partial response or stable disease, the combination of DS and variation of SUVmean allowed identification of three groups with different prognosis: patients with DS1–3 and those with DS4–5 and decreased SUVmean had similar 1‐year PFS of 62% and 61%, whereas patients with DS4–5 and increased SUVmean had a poorer 1‐year PFS of 33% ( p = .04). Conclusions: PET parameters and association of DS and variation of SUVmean at 30 days could help in identify patients at high risk of CAR T‐cell failure. Lay summary: This is a single‐center prospective study on 47 lymphoma patients receiving commercial chimeric antigen receptor T‐cell therapy aimed to evaluate the prognostic value of baseline and after infusion 18 F‐fluorodeoxyglucose positron emission tomography. Among patients in partial remission or stable disease at day 30, the authors observed two subgroups with significantly different prognosis; patients with Deauville score (DS)4–5 and a concomitant reduction of standardized uptake value (SUV)mean had higher probability of long‐lasting response than those with DS4–5 and an increase of SUVmean . Abstract : The combination of qualitative and quantitative positron emission tomography parameters assessed at day 30 after chimeric antigen receptor T‐cell treatment could help identify prognostically different subgroups among patients with partial response or stable disease. At day 30, patients in partial remission (PR)/stable disease (SD) and a concomitant reduction of standardized uptake value (SUV)mean had higher probability of long‐lasting response than those with PR/SD and an increase of SUVmean .